2009
DOI: 10.1021/ja805037p
|View full text |Cite
|
Sign up to set email alerts
|

All-Atom Model for Stabilization of α-Helical Structure in Peptides by Hydrocarbon Staples

Abstract: Recent work has shown that the incorporation of an all-hydrocarbon "staple" into peptides can greatly increase their α-helix propensity, leading to an improvement in pharmaceutical properties such as proteolytic stability, receptor affinity and cell-permeability. Stapled peptides thus show promise as a new class of drugs capable of accessing intractable targets such as those that engage in intracellular protein-protein interactions. The extent of α-helix stabilization provided by stapling has proven to be subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 61 publications
(105 reference statements)
8
108
0
Order By: Relevance
“…[47][48][49][50][51] MD simulations were carried out for a set of such peptides that were designed to bind to MDM2. 53 We find that the good binders assume helicity in solution as has also been demonstrated in other simulation studies 53,54 and now we also show that they assume extended helicity when bound to MDM2. In contrast, the poor binders are less helical.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[47][48][49][50][51] MD simulations were carried out for a set of such peptides that were designed to bind to MDM2. 53 We find that the good binders assume helicity in solution as has also been demonstrated in other simulation studies 53,54 and now we also show that they assume extended helicity when bound to MDM2. In contrast, the poor binders are less helical.…”
Section: Discussionsupporting
confidence: 88%
“…30 In order to understand the observations of Verdine and colleagues, we perform all-atom molecular dynamics (MD) simulations. Recent MD studies of the peptides for inhibiting MDM2, 53 and BH3, 54 found that the helical content of the peptides did relate to the binding affinity. However, these studies were focused on exploring the conformations of the peptides alone.…”
Section: Resultsmentioning
confidence: 99%
“…Approaches to stabilize peptide helicity include the cross-linking of amino acid side chains by using a disulfide, [4a] thioether, [4b,c] oxime, [4d] lactam, [5,6] or hydrocarbon "staple"; [7,8] the replacement of an a-helix-defining (i, i + 4) hydrogen bond with a covalent bond; [9,10] the use of b-amino acids or peptoids as helical foldamers; [11] and the use of conformationally restricted organic scaffolds [12] or metal-ion clips [13] in helix mimics. Each strategy has limitations, such as conformational plasticity, hydrophilicity, synthetic difficulties, inaccurate mimicry of H-bonds, or unidirectional helix induction.…”
mentioning
confidence: 99%
“…Next, two cyclic units placed back-to-back (7,8) or spaced by 2 or 9 residues (9, 6) were examined for the potential to correct distortions observed around Asp5 in peptides 1 and 4. We have reported bicyclic peptides Ac-(cyclo-1,5;6,10 (9), [6c] which appeared to be a-helical, but now decided to look more closely at their structures for subtle defects, as all three structures 7-9 had residues at positions corresponding to defects in 1 and 4 ( Figure 5 A, gray residues).…”
mentioning
confidence: 99%
“…Besides the noticeable helix stabilization, peptide 35 was 40-fold more resistant against trypsin digestion than its linear (unmetathesized) counterpart [50]. To address the need for a more in-depth understanding on how peptide stapling stabilizes peptide helices, all-atom Monte Carlo folding simulations were performed [53]. These insights are currently explored as tools in chemical biology or to improve the drug-like properties of therapeutically relevant stapled peptides [54][55][56][57][58][59][60].…”
Section: Stabilization Of α-Helices and β-Turns In Peptidesmentioning
confidence: 99%